2020
DOI: 10.1089/ten.tea.2019.0068
|View full text |Cite
|
Sign up to set email alerts
|

The Effects ofROCKInhibition on Mesenchymal Stem Cell Chondrogenesis Are Culture Model Dependent

Abstract: Rho-associated protein kinase (ROCK) signaling correlates with cell shape, with decreased cell spreading accompanied by decreased ROCK activity. However, how cell shape and ROCK activity impact the chondrogenesis of mesenchymal stem cells (MSCs) remains inconclusive. Here we examine the effects of ROCK inhibition on human MSC chondrogenesis in four different culture models, including three-dimensional (3D) microribbon (mRB) scaffolds, two-dimensional hydrogel (2D-HG) substrates, 3D hydrogels (3D-HGs), and pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Increased chondrogenesis was always accompanied by enhanced N-cadherin expression, suggesting N-cadherin as a robust marker to, for example, select culture conditions that promote chondrogenesis. Interestingly, in another study [ 199 ], ROCK inhibition had minimal effects in the 2D or 3D models and varying the polymer used did not change the chondrogenic response to ROCK inhibition within each culture model. However, ROCK inhibition decreased chondrogenesis in a newly developed gelatin-based microribbon (μRB) model, which is a highly macroporous scaffold, in which encapsulated cells attach to the surface of individual μRBs and exhibit rapid cell spreading upon encapsulation [ 200 ].…”
Section: Differential Msc Behavior In 2d Vs 3dmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased chondrogenesis was always accompanied by enhanced N-cadherin expression, suggesting N-cadherin as a robust marker to, for example, select culture conditions that promote chondrogenesis. Interestingly, in another study [ 199 ], ROCK inhibition had minimal effects in the 2D or 3D models and varying the polymer used did not change the chondrogenic response to ROCK inhibition within each culture model. However, ROCK inhibition decreased chondrogenesis in a newly developed gelatin-based microribbon (μRB) model, which is a highly macroporous scaffold, in which encapsulated cells attach to the surface of individual μRBs and exhibit rapid cell spreading upon encapsulation [ 200 ].…”
Section: Differential Msc Behavior In 2d Vs 3dmentioning
confidence: 99%
“…However, this comparison is difficult, as the substrates used in both studies had comparable stiffnesses but different biomaterial types. Regardless, we identified one study that assessed hMSC chondrogenesis on the polymers’ gelatin, chondroitin sulfate, hyaluronic acid, and polyethylene glycol in 2D vs. 3D [ 199 ]. This study demonstrated that the expression levels of the chondrogenic differentiation markers collagen type II, ACAN, and SOX9 were comparable in 2D vs. 3D but much higher in 3D, and this behavior was observed for all four polymers.…”
Section: Differential Msc Behavior In 2d Vs 3dmentioning
confidence: 99%
See 1 more Smart Citation
“…4F) and Cdh2 (N-Cadherin) (Fig. 4G) and are two markers of early chondrogenesis [37], and Cdh2 upregulation is a robust marker of early chondrogenic differentiation [38]. We noted signi cantly decreased expression of Cdh2 in Wdpcp-cKO versus control (Fig.…”
Section: Loss Of Wdpcp Disrupts Early Chondrogenesismentioning
confidence: 70%
“…Interestingly, the level of SOX9 was reduced with the increased formation of cell aggregates. It has been reported that the cells in pellets expressed significantly lower levels of N‐cadherin than monolayer culture 47 and N‐cadherin has been shown to be a critical regulator of chondrogenesis 48‐50 . In particular, our previous study showed that immunoblocking of N‐cadherin suppressed SOX9 expression 51 .…”
Section: Discussionmentioning
confidence: 85%